Discours of Sustainability and their Inclusion in the Organizational Context (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.1.5061.147-186.The critique of industrial capitalism and the recognition of the importance of the environment in the global economy was crucial to the sustainability discourse is an expression of order common in the organizational context. Analyze the construction of the discourse of sustainability becomes relevant so that we can study the issue within organizations. From a literature review, this study aims to reflect on the discourse of sustainability as an institutional and media discourses, and its place in the organizational context. The discourse of sustainability is possible to unveil part of an organizational reality, showing interest groups, conflicts and power relations. The discourse of sustainability and its place in the organizational context is constructed and constantly reconstructed in a context dominated by economic interests.